Дизайн виставкових експозицій у сучасній проектно-художній діяльності - Северин, Віктор Дмитрович; Северин, Надія Василівна; Проценко, Ольга Петрівна (Національна академія керівних кадрів культури і мистецтв, 2020)
Мета роботи. Дослідження пов‘язане з визначенням основних складових виставкового дизайну та новітніх технологій, які використовуються у організації виставкових просторів. Метою даної роботи є з‘ясування ролі дизайну виставкових експозицій у проектно-художній діяльності. Методологія. Для дослідження концепту «виставковий дизайн» було використано загальнонаукові методи: аналіз і синтез, індукцію і дедукцію, опис. Метод системно-функціонального аналізу допоміг дослідити дане явище у взаємозв‘язку з іншими галузями дизайну: архітектурою, дизайном інтер‘єрів, графічним дизайном, середовищним дизайном. Міждисциплінарний та компа-ративний підходи спонукали до об‘єднання різних концепцій для визначення місця виставкового дизайну в інформаційно-комунікативному просторі сучасного суспільства. Провідними для дослідження виставкового дизайну стали герменевтичний та феноменологічний методи. Наукова новизна. Вперше здійснено ґрунтовне дослідження концепту «виставковий дизайн» та з‘ясовано його роль і функції у сучасному суспільстві. Наведені приклади показують, що виставкова експозиція візуалізує і демонструє економічні та культурні досягнення однієї чи кількох країн. Висновки. Реалізація міждисциплінарного підходу до створення проекту виставки дає можливість переда-вати інформацію на декількох рівнях. Виставковий дизайн є синтезом усіх видів дизайну – архітектурного, середовищного, промислового, ландшафтного, графічного. Завдяки дизайну виставка інтегрується у дизайн інтер‘єрів та архітектуру оточуючого середовища, стає способом просування товарів народного споживання і художніх творів.

Purpose of Article. The research is related to the study of the main components of the exhibition design and innovative technologies that are used in the organization of exhibition spaces. The purpose of this work is to determine the role of the design of exhibits in modern design and artistic activities. Methodology. Common scientific methods, namely analysis, and synthesis, induction and deduction, description, are used to study the exhibition design. The meth-od of system-functional analysis helped to investigate this phenomenon in interconnection with other areas of design: architecture, interior design, graphic design, and environmental design. Interdisciplinary and comparative approaches have led to the unification of various concepts to identify the role of exhibition design in modern information and commu-nicative space, namely art studies and aesthetics, social philosophy, and semiotics. Hermeneutical and phenomenologi-cal methods are basic for the research of exhibition design. Interdisciplinary and comparative approaches have led to the integration of different concepts to determine the place of exhibition design in the informational and communicative space of modern society. Hermeneutical and phenomenological methods became the leading examples of the exhibition de-sign. The scientific novelty of the work consists of thorough research of the concept of ―exhibition design" and clarifica-tion of its role and functions in modern society. The examples presented show that the exhibition exposition visualizes and demonstrates the economic and cultural achievements of one or more countries. Conclusions. The implementation of the interdisciplinary approach to the design of the exhibition gives the opportunity to transmit information at several levels. Exhibition design is a synthesis of all kinds of design - architectural, environmental, industrial, landscape, graphic. Thanks to the design, the exhibition integrates into the design of interiors and the architecture of the environment, and it becomes a way of promoting consumer goods and artistic works.
Design of exhibition expositions in modern design and art activities
Keywords: виставковий дизайн; предметно-просторове середовище; культуркомунікативний простір; exhibition design; object-spatial environment; cultural space; communicative space; information sphere; communicative sphere